2015
DOI: 10.15713/ins.idmjar.32
|View full text |Cite
|
Sign up to set email alerts
|

Impact of screw retained versus cement retained implant-supported prosthesis on peri-implantitis:A systematic review and meta-analysis

Abstract: Purpose: The aim of this study was to test the signifi cant diff erences of the marginal bone loss (MBL) between screw retained versus cemented prosthesis. Materials and Methods: A comprehensive electronic searching in PubMed and Cochrane databases up to July 2015 with language restriction to English only. We include any randomized controlled trials compare between screw retained versus cemented retained implant prosthesis regarding MBL. In addition, a manual searching was performed for related journals from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…However, our findings are comparable to studies in the Asian context, which reported awareness levels in the range of 41.7 to 47%. [6][7][8]10,13,14 In this study, nearly half of the respondents were moderately informed to well informed regarding the options of replacement of missing teeth. This highlights the need to increase awareness among the people regarding implant-related treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings are comparable to studies in the Asian context, which reported awareness levels in the range of 41.7 to 47%. [6][7][8]10,13,14 In this study, nearly half of the respondents were moderately informed to well informed regarding the options of replacement of missing teeth. This highlights the need to increase awareness among the people regarding implant-related treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…11,20,21 For this reason, Sailer et al 11 raised the possibility of screwed protheses becoming the most popular even if both methods had presented high survival rate, which makes it harder for us to define the best option. In addition, other studies 19,23,24,25 did not observe significant difference between retention methods when considering marginal bone resorption, as they are within normal standards, which reinforces the importance of complete subgingival removal of cement excesses to prevent peri-implantitis and marginal bone loss.…”
Section: Summary Of the Findingsmentioning
confidence: 57%
“…The condition of peri-implantitis imposes worst complications by destroying the peri-implant tissue and bone loss concerned with both cement-retained and screwretained prosthesis. 5,6 Weber et al 7 compared the responses of peri-implant soft tissue between cement-retained and screw-retained restoration. Favorable results in terms of bleeding on probing and low plaque index were obtained for screw-retained restorations as compared to cementretained restorations.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, Al-Fahd et al 5 showed conflicting results concerning the implant reconstruction using a screw and cement-based restorations. Similarly, a systematic study of Sailer et al 8 showed that cement dental implant poses severe biological complications, which contradicts the results of de Brandao et al 9 which revealed no difference between the two types of implants.…”
Section: Introductionmentioning
confidence: 99%